2020
DOI: 10.1111/bcp.14627
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of tailored dosing schedule for eculizumab based on therapeutic drug monitoring: Lessons from a prospective multicentric study

Abstract: Eculizumab is an anti-C5 monoclonal antibody approved for rare diseases including atypical haemolytic-uraemic syndrome. The maintenance phase dosing regimen is identical for all adult patients: 1200 mg every 2 weeks. Recent studies reported an overexposure in many patients when considering a target trough concentration range of 50-100 mg/L. The aim of the present work was to validate the feasibility of therapeutic drug monitoring of eculizumab in atypical haemolyticuraemic syndrome patients.Methods: We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 34 publications
(44 reference statements)
3
23
0
2
Order By: Relevance
“…10 Other studies have demonstrated similar findings of supratherapeutic eculizumab levels in adult and pediatric populations 11,12 ; yet, others have also demonstrated success in decreasing the frequency of eculizumab dosing by monitoring complement serology. [13][14][15] Although other studies have reported the use of AH50 and total complement activity (CH50) to determine interval frequencies, ours is the first report using both C5 and mass spectrometric assessment of eculizumab to guide a personalized dosing strategy. We decided to implement C5 as a clinical test for eculizumab monitoring given its higher specificity.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…10 Other studies have demonstrated similar findings of supratherapeutic eculizumab levels in adult and pediatric populations 11,12 ; yet, others have also demonstrated success in decreasing the frequency of eculizumab dosing by monitoring complement serology. [13][14][15] Although other studies have reported the use of AH50 and total complement activity (CH50) to determine interval frequencies, ours is the first report using both C5 and mass spectrometric assessment of eculizumab to guide a personalized dosing strategy. We decided to implement C5 as a clinical test for eculizumab monitoring given its higher specificity.…”
Section: Discussionmentioning
confidence: 92%
“… 15 , 16 Pharmacokinetic modeling in one study showed that body weight and male gender increased eculizumab elimination clearance and suggested that trough concentrations of less than 100 μg/mL of eculizumab may be more likely in the case of the highest bodyweight tested (90 kg). 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therapeutic monitoring of ECUL has allowed cost-savings along with improved quality of life for patients by extending infusion intervals when drug concentrations are above therapeutic thresholds, with patients maintaining complete complement activity blockage [4] , [5] , [6] , [7] . Although not yet common practice, we expect that therapeutic monitoring of RAVUL may similarly assist in personalizing therapy regimens and contribute to improved outcomes.…”
Section: Introductionmentioning
confidence: 99%